Polyether-Based Supramolecular Electrolytes With Two-Dimensional Boroxine Skeleton - Yoshizawa-Fujita, Masahiro; Horiuchi, Shunsuke; Uemiya, Tamao; Ishii, Jun; Takeoka, Yuko; Rikukawa, Masahiro (Frontiers in Energy Research, 2021)
Solid polymer electrolytes mainly based on polyethers have been actively investigated for over 40 years to develop safe, light, and flexible rechargeable batteries. Here, we report novel supramolecular electrolytes (SMEs) composed of polyether derivatives and a two-dimensional boroxine skeleton synthesized by the dehydration condensation of 1,4-benzenediboronic acid in the presence of a polyether with amines on both chain ends. The formation of SMEs based on polyether derivatives and boroxine skeleton was confirmed by Fourier transform infrared (FT-IR) spectroscopy, X-ray photoelectron spectroscopy (XPS), powder X-ray diffraction (PXRD), and thermogravimetric (TG) analysis. Linear sweep voltammetry (LSV) and cyclic voltammetry (CV) were performed to evaluate the electrochemical stability and lithium conductive properties of SMEs with given amounts of lithium bis(trifluoromethylsulfonyl)amide (LiTFSA). The ionic conductivity of SME/LiTFSA composites increased with increasing lithium-salt concentration and reached a maximum value at a higher concentration than those of simple polyether systems. The lithium-ion transference number (tLi+) of SME/LiTFSA was higher than those of polyether electrolytes. This tendency is unusual for a polyether matrix. SME/LiTFSA composite electrolytes exhibited a stable lithium plating/striping process even after 100 cycles. The current density increased with an increasing number of cycles. The combination of ion conductive polymers and a two-dimensional boroxine skeleton will be an interesting concept for developing solid electrolytes with good electrochemical properties.